Igniting Hope in Youth from High-Risk Settings - Peterson, Thomas A. (Journal of Organizational Psychology, 2020)
Educators often find themselves in a struggle for survival and are unable to resolve their differences with challenging youth, who are given labels due to behaviors of acting out that they may display. This research explores a mentoring program that uses an alternative to traditional behavioral models in working with youth and that provides evidence-based insights into creating a community of acceptance and hope. This unique approach to mentoring embraces identity and integrity as a way of inspiring hope in youth from high-risk settings and forming intimate connections.